If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 6q + -7(2p + -9q) = 0 7p + 6q + (2p * -7 + -9q * -7) = 0 7p + 6q + (-14p + 63q) = 0 Reorder the terms: 7p + -14p + 6q + 63q = 0 Combine like terms: 7p + -14p = -7p -7p + 6q + 63q = 0 Combine like terms: 6q + 63q = 69q -7p + 69q = 0 Solving -7p + 69q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-69q' to each side of the equation. -7p + 69q + -69q = 0 + -69q Combine like terms: 69q + -69q = 0 -7p + 0 = 0 + -69q -7p = 0 + -69q Remove the zero: -7p = -69q Divide each side by '-7'. p = 9.857142857q Simplifying p = 9.857142857q
| 3+c+6=-2 | | 2x^2+14x+40=0 | | C=300-273.15 | | 5x-2(x-2)=-4+5x-6 | | 6x^2+7=85 | | 2(6x-7)=5x-2 | | 10=6-5x+4 | | 18d^2-7qg+63dq-2dg= | | -16t^2-30t+376=0 | | 9x-2x=77 | | 20x^2-93x+34=0 | | 3(-n-6)=-3(n+6) | | 12+5x=18+3 | | 7k-3k+4=8 | | Y+16.7=-49.0 | | 2*6x-7=5x-2 | | x^4+8x^3-34x^2-8x+33=0 | | n^2-4n+1=-2 | | 10x+36=11 | | -9(3n+7)=-252 | | 7x^2-7=245 | | 4-b=-7(-b-4) | | 4x+5y+6x= | | f(x)=[x] | | 22+21x=25x-2 | | 3(t-16)+5=17 | | 5n-1=2(n+10) | | 2y+6+(-3x)+(-4y)-x= | | 180=3x-6+130+3x+4 | | -7x^2=-70 | | -38+2x=8(x-7) | | 32.50=14-4n+2n |